Water homeostasis gene expression in the kidney of broilers divergently selected for water conversion ratio - Kentu Lassiter; Loujain Aloui; Elizabeth S. Greene; Marciela Maqaeda; Travis Tabler; Sami Dridi; Robert F. Wideman, Jr.; Sara Orlowski; Walter G. Bottje (Poultry Science)
Divergent selection of broilers for water conversion ratio has established and high-(HWE) and low- water efficient (LWE) broiler lines. Two 2 × 2 factorial experiments were conducted to assess the gene expression profile of systems involved in renal water homeostasis. In Exp. 1, male and female HWE and LWE broilers were individually phenotyped between 4 and 6 wks of age to determine growth performance and water conversion ratio (g water intake/g body weight gain). Kidney samples were obtained from 5 males and 5 females from each line. In Exp. 2, HWE and modern random bred (MRB) broilers were placed in 12 controlled-environmental chambers (2 floor pens/chamber, 6 chambers/line, 11 birds per pen, 132 birds/line) on day of hatch. The broilers were brooded at thermoneutral temperatures from 0 to 4 wks. From 4 to 7 wks, broilers were maintained at thermoneutral (TN, 25 °C) or exposed to cyclic heat stress (HS, 35 °C, 8h/day) conditions. Body weight, feed intake, and water intake were recorded. Kidney samples were collected, flash frozen in liquid nitrogen, and kept at -80 °C for gene expression analysis. Data were analyzed by Two-way ANOVA and means compared by Tukey's HSD multiple comparison test. Molecular analyses from Exp. 1 showed that the renal expression of arginine vasopressin (AVP), angiotensinogen (AGT), angiotensin II receptor type 1 and 2 (AT1/2), sodium-potassium ATPase subunit B1 (ATP1B1), and aquaporin 3 (AQP3) were upregulated in HWE compared to the LWE line. In contrast, mRNA expression of mesotocin receptor (MTR), AT1/2, AQP1/2, and occludin were significantly higher in females than in males. In Exp. 2, target genes were regulated in environment and/or line-dependent manner. The renal expression of heat shock proteins 70 and 90, AVP receptor 2 (AVPR2), AGT, renin, AT1/2, and AQP1was significantly upregulated in HS compared to TN birds, however AVPR2 expression was significantly higher in HWE compared to MRB birds. Together, the up-regulation of AVP, the renin-angiotensin system (RAS), and AQP in HWE, female, or under HS conditions suggests a better renal water reabsorption to support water use efficiency.